Discovery of non-classical complex models between a cationic water-soluble pillar[6]arene and naphthalenesulfonate derivatives and their self-assembling behaviors. Issue 20 (2nd May 2019) - Wang, Mengbin; Zhou, Jiong
Abstract : Non-classical complex models of a cationic water-soluble pillar[6]arene with naphthalenesulfonate derivatives and their self-assembling behaviors were discovered. Abstract : Molecular recognition based on cationic water-soluble pillar[ n ]arenes shows considerable advantages in their application in biological and environmental systems, such as excellent anion-binding ability and antimicrobial properties. Unique complex models are discovered in this work where a cationic water-soluble pillar[6]arene binds with disodium 1, 5-naphthalenedisulfonate and disodium 2, 6-naphthalenedisulfonate at the ratio of 1 : 2, which is proven by results from nuclear magnetic resonance spectroscopy, isothermal titration calorimetry, fluorescence spectroscopy experiments and transmission electron microscopy.